2014
DOI: 10.1111/jfd.12246
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a ranavirus from koi, Cyprinus carpio L., experiencing mass mortalities in India

Abstract: We investigated mass mortalities of koi, Cyprinus carpio Linnaeus, 1758, experienced in South Indian fish farms by virus isolation, electron microscopy, PCR detection, sequencing of capsid protein gene and transmission studies. Samples of moribund koi brought to the laboratory suffered continuous mortality exhibiting swimming abnormalities, intermittent surfacing and skin darkening. Irido-like virus was isolated from the infected fish in the indigenous snakehead kidney cell line (SNKD2a). Icosahedral virus par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 39 publications
(68 reference statements)
2
51
0
1
Order By: Relevance
“…A SCRV strain isolated from moribund hatchery-reared largemouth bass reared in China was found to be highly lethal to largemouth bass (Deng et al 2011 ); however, little or no mortality was observed in seven other species tested including koi ( Cyprinus carpio ; Table 3 ). In contrast, a recent mass mortality event among farmed koi in southern India was attributed to a strain of SCRV (George et al 2014 ), although the authors did not provide a detailed description of viral-induced pathology.…”
Section: Santee-cooper Ranavirusmentioning
confidence: 86%
See 3 more Smart Citations
“…A SCRV strain isolated from moribund hatchery-reared largemouth bass reared in China was found to be highly lethal to largemouth bass (Deng et al 2011 ); however, little or no mortality was observed in seven other species tested including koi ( Cyprinus carpio ; Table 3 ). In contrast, a recent mass mortality event among farmed koi in southern India was attributed to a strain of SCRV (George et al 2014 ), although the authors did not provide a detailed description of viral-induced pathology.…”
Section: Santee-cooper Ranavirusmentioning
confidence: 86%
“…The reasons for the emergence of ranaviruses as pathogens of fi nfi sh within both natural and managed populations are unknown. However, the repeated detection of the same fi nfi sh ranaviruses (e.g., SCRV) around the globe suggests that the international movement of live animals and their products likely plays an important role in the occurrence of these epizootics (Hedrick and McDowell 1995 ;Plumb and Zilberg 1999a ;Grant et al 2005 ;Schramm and Davis 2006 ;Deng et al 2011 ;George et al 2014 ).…”
Section: Ranaviruses Infecting Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…It cannot be assumed that the virus reported here was an LCDV, as ranaviruses (Pozet et al 1992, Bayley et al 2013, Chinchar & Waltzek 2014, George et al 2015 and megalocytiviruses (Subramaniam et al 2012, Waltzek et al 2012) also infect fish, are very non-host specific (Mao et al 1997, Hyatt et al 2000, Bayley et al 2013, and a single host genus such as grouper (Epinephalus) may be infected with ranavirus (Peng et al 2015) and LCDV (Huang et al 2015). Geographic occurrence rather than host group specificity may be as important in determining which host groups are infected (Mao et al 1997, Hyatt et al 2000, Bayley et al 2013.…”
Section: Discussionmentioning
confidence: 89%